131k views
1 vote
What is the inverse of the statement below?

XY
A. y X
B. 2X
C. yx
O
o
D. Xy

What is the inverse of the statement below? XY A. y X B. 2X C. yx O o D. Xy-example-1
User Guicara
by
4.9k points

1 Answer

7 votes

9514 1404 393

Answer:

B. ¬x ⇒ ¬y

Explanation:

The inverse negates both the antecedent and the conclusion, leaving them in the same relationship with the implication arrow.

What is the inverse of the statement below? XY A. y X B. 2X C. yx O o D. Xy-example-1
User Jaffar Ramay
by
5.3k points